Tingkat Keausan Cylinder Liner Akibat Beban Gesek Pada Variasi Suhu Permukaan Basah 30 C - 250 C - Baryudha, Eko Febriyanto; Widiyarta, I Made; Parwata, I Made (Teknik Desain Mekanika; Vol 10 No 3 (2021): Juli 2021 : Teknik Desain Mekanika, 2021)
Abstract The cylinder liner is a component located in the cylinder block of an internal combustion engine. During the combustion process, the cylinder liner receives high pressure and heat and friction from the piston rings. This condition can cause wear on the cylinder liner surface. The presence of lubrication provided on the contact surface between the cylinder liner and the piston ring can prevent increased wear of the cylinder liner. In this study, the wear test on the cylinder liner due to piston ring friction was carried out by varying the surface temperature of the cylinder liner from 30? to 250?. The test results show a decrease in wear even though the surface temperature increases from 30? to 250?. The level of wear that occurs decreases from 0.000006 gr/cycle to 0.000003 gr Keyword : Cylinder liner, Friction Load, Wear